VESICOVAGINAL AND RECTOVAGINAL FISTULAS: 12-YEAR RESULTS OF SURGICAL TREATMENT - Ayaz, Attiya; Nisa, Rahat un; Anwar, Sadia; Mohammad, Taj (Journal of Ayub Medical College Abbottabad, 2012)
Background: Although the magnitude of obstetric fistulae (OF) is reported to have decreased in industrialised countries, it is still a major problem in developing countries especially the fistulae resulting from obstructed labour. Vesico-vaginal fistulae (VVF) are the most common and the most frequent type of urogenital fistulas. In most cases, surgery is required for treatment. The aim of this study was to analyse the results of surgical treatment of VVF and Rectovaginal Fistulae (RVF) in a tertiary level institution over 12 years period. Methods: This retrospective study was conducted at Ayub Teaching Hospital, and Women and Children Hospital, Abbottabad. It included records of a total of 74 patients who were surgically treated from 2001 to 2012. Results: Cause of VVF was obstructed labour in 81.08% of cases, and it was iatrogenic in 18.92% cases. In the surgical treatment of primary VVF transvaginal approach was used in 91.9%, while transabdomenal approach was used in 2.7% cases. In 54.1% of cases the VVF healed after a single surgical intervention, while in 45.9% cases more-than-one operations were required. Conclusion: Birth trauma is still a major cause of VVF/RVF in our region. Prevention is possible with provision of sufficient health care and public awareness. Successful repair is possible with 1st surgery. Keywords: Obstetric fistulae, vesicovaginal fistulae, rectovaginal fistulae, iatrogenic, repair, women